From Bacteria to Zooplankton: An Integrative Approach Revealing Regional Spatial Patterns During the Spring Phytoplankton Bloom in the Southern Bight of the North Sea - Aubert, Anaïs; Beauchard, Olivier; de Blok, Reinhoud; Artigas, Luis Felipe; Sabbe, Koen; Vyverman, Wim; Martínez, Luz Amadei; Deneudt, Klaas; Louchart, Arnaud; Mortelmans, Jonas; Rijkeboer, Machteld; Debusschere, Elisabeth (Frontiers in Marine Science, 2022)
Plankton comprises a large diversity of organisms, from pico- to macro-sized classes, and spans several trophic levels, whose population dynamics are characterised by a high spatio-temporal variability. Studies integrating multiple plankton groups, in respect to size classes and trophic levels, are still rare, which hampers a more thorough description and elucidation of the full complexity of plankton dynamics. Here, we present a study on the spatial variability of five in-situ monitored plankton components, ranging from bacteria to meso-zooplankton, and using a complementary set of molecular, chemical and imaging tools, with samples obtained during the phytoplankton spring bloom in the hydrodynamically complex Southern Bight of the North Sea. We hypothesised that while generally recognized spatial gradients in e.g. salinity, turbidity and nutrients will have a strong impact on plankton spatial distribution patterns, interactions within the plankton compartment but also lag effects related to preceding bloom-related events will further modulate spatial structuring of the plankton. Our study indeed revealed an overriding imprint of regional factors on plankton distribution patterns. The dominant spatial pattern mainly reflected regional differences in dissolved inorganic nutrients and particulate matter concentrations related to differences in phytoplankton bloom timing between the two main regions of freshwater influence, the Thames and the Scheldt-Rhine-Meuse. A second major pattern corresponded to the expected nearshore-offshore gradient, with increasing influence of low turbidity and low nutrient Atlantic waters in the offshore stations. Environmental forcing on specific plankton groups and inter-plankton relationships also appeared to drive plankton distribution. Although the marine plankton comprises heterogeneous functional groups, this study shows that multiple planktonic ecosystem components can be parts of common spatial gradients and that often neglected small planktonic organisms can be key drivers of such gradients. These analytical outcomes open questions on regional and seasonal reproducibility of the highlighted gradients.